Human Factors and Organizational Issues: Contributions from 2023 - Solomonides, Anthony; Senathirajah, Yalini (Yearbook of Medical Informatics, 2024)
Objectives: To review publications in the field of Human Factors and Organisational Issues (HF&OI) in the year 2023 and to assess major contributions to the subject.Methods: A bibliographic search was conducted following further refinement of standardized queries used in previous years. Sources used were PubMed, Web of Science, and referral via references from other papers. The search was carried out in February 2024, and (using the PubMed article type inclusion functionality) included clinical trials, meta-analyses, randomized controlled trials, reviews, case reports, classical articles, clinical studies, observational studies, comparative studies, and pragmatic clinical trials.Results: Among the 513 returned papers published in 2023 in the various areas of HF&OI, 87 were identified for full review that resulted in a shortlist of 12 finalists and finally three best papers from among these. As in previous years, topics showed development including increased use of Artificial Intelligence (AI) and digital health tools, advancement of methodological frameworks for implementation and evaluation as well as design, and trials of specific digital tools.Conclusions: Recent literature in HF&OI continues to focus on both theoretical advances and practical deployment, with focus on areas of patient-facing digital health, methods for design and evaluation, and attention to implementation barriers.
Keywords: International Medical Informatics Association Yearbook; Human Factors; Organizational issues; Digital Health; Usability